Peran Lembaga Swadaya Masyarakat PPAP Seroja Dalam Pelaksanaan Program Kota Layak Anak PadaLingkungan Pendidikan Anak Jalanan Di Kota Surakarta - Diyan Syahputra, Musrifin, Drs. Budi Sutrisno, M.Pd (2016)
This study aims to describe the role of the Institute PPAP Seroja's related in the implementation of the Child-friendly City Program (KLA) in the educational environment of street children in Surakarta. The research is a qualitative research with an ethnographic approach. Subjects in this study were PPAP Seroja Institution administrators, the street children, and the parents of street children fostered Institute Seroja. Techniques for analiyzing data used data collection, reduction of data, presentation of data, and verification of data. By triangulation techniques and resources. The results obtained illustrate that 1) Institute of PPAP Seroja through the role and the Government of Surakarta through the Child-friendly City Program (KLA) both have programs that support each other. The our program of PLK School's, street children can obtain education academic, life skills and mental development, diploma Packet, and reduce the intensity of street children for a long road,. 2) Barriers experienced PPAP Seroja's institution categorized into two, First, the barriers that come from within (internal) such as, lack of human resources, lack of funding and lack of utilization of the facilities available. Second, the barriers that come from outside (external) include lack of attention from the government to the institution that concerned education for street children, the lack of support in the activities and programs implemented institution from relevant agencies, as well as poor coordination for the development of the Child-friendly City (KLA) program's. Recommendations are given for the government is the need for more coordination the implementation of the program, so that good management can be realized in maintaining the Child-friendly City Surakarta as the best in Indonesia.